PERBANDINGAN ANTARA PERBAIKAN KLINIS PENDERITA STROKE ISKEMIK AKUT DENGAN KADAR KALIUM SERUM NORMAL RENTANG BAWAH YANG MENDAPAT TERAPI STANDAR DENGAN YANG MENDAPAT TERAPI STANDAR DITAMBAH KALIUM - Safat Wahyudi, Paulus Sugianto (Neurona Majalah Kedokteran Neuro Sains, 2012)
INTRODUCTION POTASSIUM HAS MANY BENEFICIAL EFFECTS ON VARIOUS CARDIOVASCULAR AND CEREBROVASCULAR DISEASES INCLUDING STROKE THROMBOTIC PROCESS IS CLOSELY ASSCOCIATED WITH BIOLOGY OF PLATELET WHERE POTASSIUM PLAYS AN IMPORTANT ROLE IN SUPPRESSING ITS ACTIVITY ADDITIONAL TREATMENT OF POTASSIUM TWICE DOSE OF DAILY INTAKE FOR 3 CONSECUTIVE DAYS WILL DECREASE THE ACTIVITY OF PLATELET IN HUMAN ADDITIONAL POTASSIUM TREATMENT IS ALSO SAID TO DECREASE INTERLEUKINE1 IL1 LEVEL WHICH TREMENDOUSLY INCREASE DURING CEREBRAL ISCHEMIA AIM OF THIS STUDY IS TO FIND THE DIFFERENCE OF CLINICAL IMPROVEMENT ON ACUTE ISCHEMIC STROKE PATIENTS RECEIVING STANDARD TREATMENT AND STANDARD TREATMENT PLUS POTASSIUM